The Combined Effect of Zataria multiflora Boiss. and Cinnamomum zeylanicum Nees. Essential Oil on the Growth of Bacillus cereus in a Food Model System - Z Mashak; B Moradi; B Moradi (Institue of Medicinal Plants, ACECR, 2012)
Background: Bacillus cereus is a spore-forming food-borne pathogen often associated with food products such as meat, vegetables, soup, rice, and milk and other dairy products. The use of plant-derived antimicrobial compounds such as Zataria multiflora Boiss. and Cinnamomum zeylanicum Nees. essential oils as natural preservatives inhibits the growth of several pathogens. Objective: The objective of this survey is evaluation the antibacterial combination effect of multiflora Boiss. and Cinnamomum zeylanicum Nees. essential oils on Bacillus cereus in a food model. Methods: Effects of different concentrations of Zataria multiflora Boiss. and Cinnamomum zeylanicum Nees. essential oils on growth of Bacillus cereus were evaluated in commercial barely soup in two storage temperature (10 and 25°C) at certain intervals. Results: The growth of Bacillus cereus was significantly decreased by Zataria multiflora Boiss. essential oil 45 µl 100 ml-1 concentration, combination with Cinnamomum zeylanicum Nees. essential oil 30µl 100ml-1 in 10°C(p < 0.05). In 25°C by Zataria multiflora essential oil 30 and 40µl 100ml-1, the growth of B. cereus was lower significantly (p < 0.05). Conclusion: The combination of Zataria multiflora Boiss. essential oil and Cinnamomum zeylanicum Nees. essential oils in 10°C, and Zataria multiflora single in 25°C exhibits inhibitory effects on growth of B. cereus. Combination of these essential oils together in small amounts can inhibit growth of B. cereus significantly so be maintain the acceptable sensory properties of foods.